Coupled system thermal-hydraulic/CFD analysis of a protected loss of flow transient in the MYRRHA reactor. (August 2018) - Toti, A.; Vierendeels, J.; Belloni, F.
Highlights: A full system thermal-hydraulic/CFD coupled model of MYRRHA is developed. The coupling method is based on domain decomposition and implicit numerical scheme. A novel application of the Quasi-Newton method is proposed for multi-domain problems. The tool is applied to a protected loss of flow (PLOF) transient. Abstract: Within the MYRRHA (Multi-purpose hYbrid Research Reactor for High-tech Applications) project, the Belgian Nuclear Research Centre SCKCEN is developing and designing a flexible irradiation facility, configured as an accelerator driven system (ADS) with a MOX fueled reactor core, able to operate in both critical and sub-critical modes. The system design features a compact pool-type primary cooling system operating with molten Lead-Bismuth Eutectic (LBE). With regard to the thermal-hydraulic design and safety assessment of the installation, a major challenge is represented by the complex coolant flow field characterizing the large open regions of the primary vessel, namely the cold and hot plenum, with the presence of pronounced three-dimensional phenomena that may impact the evolution of accidental transients such as loss of flow events. In order to have a realistic representation of such effects, a coupled system thermal-hydraulic/CFD model of the MYRRHA reactor is developed and presented in this paper. The proposed multi-scale methodology, which couples the 1D system code RELAP5-3D to the CFD code FLUENT, is based on domain decomposition and a novel implicit numerical scheme is developed. The coupled reactor-scale computational model is applied in this work to the analysis of a postulated protected loss of flow (PLOF) accident, and preliminary validated against RELAP5-3D stand-alone solution data. The results of the analysis were found in agreement, demonstrating the capability of the tool to perform integral simulation taking into account 3D flows and local phenomena.